EXAMINATION OF MENTAL TOUGHNESS SITUATIONS OF ATHLETES INTERESTED IN TEAM AND INDIVIDUAL SPORTS - RECEP FATİH KAYHAN; SERKAN HACICAFEROĞLU; HAYRİ AYDOĞAN; İBRAHİM ERDEMİR (ümit doğan üstün, 2018)
This study conducted to determine the perception of athletes interested in team and individual sports related to mental toughness situations. In the study cross-sectional method used. The study sample consisted of 155 individual or team sport participants from Rize province. In the study in order to determine the mental toughness perceptions of the participants the Turkish version of Madrigal, Hamill and Gill (2013)'s Mental Toughness Scale used. The scale adapted into Turkish by Erdoğan in 2016. The scale is a self-report scale with 11 items anchored with 5 Likert type scale. To analyze the data first Kolmogorow-Smirnow used in order to determine the distribution of the data and then Mann Whitney U and Kruskall-Walliss tests used. According to analyze results no significant differences found on the variable mental toughness according to gender, age, sports age. Besides, although the mean rank scores of the participants' differed it was not considerable. As a result this paper showed that mental toughness of the athletes from different individual and team sports was similar in terms of gender, age and sport age. In this context, the mental training to be carried out in the direction of improving the physical and tactical training of different sports branches can be planned and implemented parallel with the results of this paper.